2016
DOI: 10.1016/j.watres.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Mainstream partial nitritation and anammox: long-term process stability and effluent quality at low temperatures

Abstract: The implementation of autotrophic anaerobic ammonium oxidation processes for the removal of nitrogen from municipal wastewater (known as “mainstream anammox”) bears the potential to bring wastewater treatment plants close to energy autarky. The aim of the present work was to assess the long-term stability of partial nitritation/anammox (PN/A) processes operating at low temperatures and their reliability in meeting nitrogen concentrations in the range of typical discharge limits below 2 mgNH4-N·normalL−1 and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
168
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 451 publications
(199 citation statements)
references
References 40 publications
(72 reference statements)
6
168
1
9
Order By: Relevance
“…Similar results were obtained in a study by Laureni et al. (), who reported higher community dynamics in suspended biomass compared to biofilm carriers in PNA reactors operated at 15°C. Such community behavior seemed to be caused by the lack of structural preservation which was available in the MBBRs.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results were obtained in a study by Laureni et al. (), who reported higher community dynamics in suspended biomass compared to biofilm carriers in PNA reactors operated at 15°C. Such community behavior seemed to be caused by the lack of structural preservation which was available in the MBBRs.…”
Section: Resultssupporting
confidence: 91%
“…Other studies reported biofilm PNA systems with Ca . Brocadia as a preferred choice at low temperature (Gilbert, Agrawal, Schwartz, Horn, & Lackner, ; Lackner & Horn, ; Laureni et al., ). Fast start‐up and stable performance of mainstream PNA systems thus relies on the inoculum composition and the reactor configuration.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of Candidatus Brocadia in these conditions is not a surprise, because Candidatus Brocadia was the dominant Anammox genus in eight systems operated close to 10°C …”
Section: Resultsmentioning
confidence: 99%
“…This study applied cold shocks for 8 h, reduced the temperature from 24 ± 2 to 5°C and applied only three consecutive shocks over 45 days with incremental increases of Anammox activity at 10°C. Conversely, Laureni et al abruptly reduced the temperature in partial nitritation/Anammox (PN/A) from 15 to 11°C for a month. Back at 15°C, these researchers reported a recovery of Anammox activity in 1 week, showing survival of Anammox under these cold shock conditions that are environmentally relevant.…”
Section: Resultsmentioning
confidence: 99%
“…ANAMMOX and DAMO processes are already studied individually Laureni et al, 2016;Lotti et al, 2015). The volumetric nitrite consumption rate of the DAMO process was shown to be not sufficient yet, and applying a membrane was suggested to increase the biomass retention .…”
Section: Recommendations For Further Researchmentioning
confidence: 99%